Bayesian programming - Bessir̈e, Pierre, author; Mazer, Emmanuel, author; Ahuactzin, Juan-Manuel, author; Mekhnacha, Kamel, author (Boca Raton : CRC/Taylor & Francis Group, 2014)
Includes bibliographical references and index